Stop fRETting the Target: Next-Generation RET Inhibitors Have Arrived - lams, Wade T. (Cancer Discov, 2018)
BLU-667 is a next-generation RET inhibitor that maximizes on-target and minimizes off-target effects. It is an exemplar of genotype-driven drug development followed by multi-histology basket trial validation that is becoming a paradigm for precision oncology. Cancer Discov; 8(7); 797–9. ©2018 AACR.